(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
In this paper the authors discuss the meaning and relevance of making plans. They conclude that although plans may initially be meaningful, paradoxically the relentless completion of plans can render life meaningless. They can inhibit personal growth if stuck to rigidly and can also inhibit our freedom and the freedom of others, freedom being a fundamental aspect of consciousness. An alternative type of plan is proposed that is more flexible and relational, and a model of the process of modifying plans in light of one’s own experience, the world and others is suggested.